Attentive-executive functioning and compensatory strategies in adult ADHD: A retrospective case series study - Ceroni, Martino; Rossi, Stefania; Zerboni, Giorgia; Biglia, Elena; Soldini, Emiliano; Izzo, Alessia; Morellini, Lucia; Sacco, Leonardo (Frontiers in Psychology, 2022)
Background Adults with ADHD exhibit a neuropsychological profile that may present deficits in many cognitive domains, particularly attention and executive functions (EFs). However, some authors do not consider executive disfunction as an important part of the clinical profile of the syndrome; this could be related to the use of inappropriate neuropsychological tests, probably not adapted and not sufficiently ecological. Moreover, new data are required on specific correlation of attentive-executive symptoms with socio-demographic factors. Therefore, the aim of this study is to analyze the neuropsychological performance of a group of adults with ADHD, also evaluating the influence of gender, age and education level. Methods We retrospectively collected health-related personal data of 40 adult ADHD patients, clinically diagnosed and evaluated via a battery of 4 neuropsychological tests and 1 self-administered questionnaire. Gender, age and years of education differences were assessed. Results Attention and EFs deficits have been highlighted mainly on the d2-R and 5-point neuropsychological tests, which therefore seem to be more sensitive in measuring the attention-executive dysfunction in an adult ADHD population, than TAP Go/No-go and ROCFT. ADHD patients also manifested subjective behavioral impulsivity disorders on BIS-11. There were no statistically significant gender differences in cognitive performance. On the contrary, younger patients performed worse on subscales TAP Go/No-go errors and 5-points number of drawings, while participants with a higher education level performed better on subscales d2-R speed of execution and d2-R errors. This supports a reduction in the number of errors and the execution time as a function of older age and a higher level of education. Finally, patients with higher education also self-reported greater impulsivity in planning. Conclusion Our preliminary findings suggest that adult ADHD is not a lifelong stable disorder, but it may change over time. Moreover, attention-executive deficits may be influenced and partially counterbalanced by experience (i.e., advancing age) and a higher level of education. This could underlie the development of specific psycho-behavioral and cognitive compensatory strategies. The use of self-administered questionnaires is therefore recommended to highlight attentional and executive difficulties that may not result in neuropsychological tests.